Sir Arthur Conan Doyle’s Sherlock Holmes Stories: Crime and Mystery from the Text to the Illustrations - Christophe Gelly (Cahiers Victoriens et Edouardiens)
This essay argues that the illustrations provided for the serial publication of the Sherlock Holmes stories by Sir Arthur Conan Doyle—mainly by Sidney Paget—constitute a significant supplement that both illustrates common ideological prejudices of the nineteenth century and undermines any complete containment of evil and crime by the investigator. This ambivalence between social conformism and a disquieting urge in Paget’s drawings appears for instance in the similitude between images of Holmes and images of Moriarty, his arch enemy, or through the stylized settings which suggest a lasting threat in the outside, non-domestic world. The specific style of the illustrations, often unrealistic and bent on euphemizing violence, also contributes to this ambivalent celebration of crime fighting that only partly hides some distrust as to its success. Eventually, by relating the topic at hand to the global debate on photographic and mechanical reproduction in the nineteenth century, it appears that the various disguises Holmes uses in the plots are rendered graphically by Paget as entirely new images of the characters, which again ambivalently points both to his mastery over crime fighting modern artefacts and to some uncertainty (generating cultural anxiety) over the question of stable identities.